Ответ:
(х-3)/(х+10)
в знаминателе х-3;
в числителе х+10
Пошаговое объяснение:
(х²+х-6)/(х²+3х-10)=(х²+х-6)/(х²+5х-2х-10)=
=(х²+х-6)/(х(х+5)-2(х+10))=
=(х²-2х+3х-6)/(х-2)(х+10)=
=(х(х-2)+3(х-2))/(х-2)(х+10)=(х+3)(х-2)/(х-2)(х+10)=(х-3)/(х+10)
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
(х-3)/(х+10)
в знаминателе х-3;
в числителе х+10
Пошаговое объяснение:
(х²+х-6)/(х²+3х-10)=(х²+х-6)/(х²+5х-2х-10)=
=(х²+х-6)/(х(х+5)-2(х+10))=
=(х²-2х+3х-6)/(х-2)(х+10)=
=(х(х-2)+3(х-2))/(х-2)(х+10)=(х+3)(х-2)/(х-2)(х+10)=(х-3)/(х+10)